The origins of the Druze religion - Bryer, D; Bryer, David R.W. (1972)
﻿ The thesis attempts to set out the doctrines of Ḥamza b. 'Alī al-Zūzanī, the earliest and most essential teachings of the Druze religion, and to indicate some of the ways in which they are related to Ismā'ilism, the source from which the Druze religion springs. The major part of the thesis is thus an edition of Ḥamza's writings, together with the writings of his lieutenant, Ismā'il b. Muḥammad al-Tamīmī and a few other pieces by the Imām al-Ḥākim and others, forming in all the first two of the six volumes of the Druze scriptures. Together with this edition is a preface; two introductory sections, one historical, one textual; a summary in English of the edited epistles and, finally, a glossary and index and bibliography. The preface considers the present state of Druze studies and gives a brief outline of the contents of the thesis. [Continued in text ...]